Neuroleptic malignant syndrome: case report and discussion - Chandran, Geethan J. (2003)
WE REPORT A CASE INVOLVING AN 81-YEAR-OLD man with schizoaffective disorder who presented with neuroleptic malignant syndrome (NMS) after an increase in his neuroleptic dose. NMS, a rare but potentially fatal complication of neuroleptic medications (e.g., antipsychotics, sedatives and antinauseants), is characterized by hyperthermia, muscle rigidity, an elevated creatine kinase level and autonomic instability. The syndrome often develops after a sudden increase in dosage of the neuroleptic medication or in states of dehydration. Treatment is mainly supportive and includes withdrawal of the neuroleptic medication and, possibly, administration of drugs such as dantrolene and bromocriptine. Complications of NMS include acute renal failure and acute respiratory failure. Given the widespread prescription of neuroleptics by physicians in a variety of fields, all physicians need to be able to recognize and appropriately manage NMS.